Wisdom of the CEO : 29 global leaders tackle today's most pressing business challenges - Dauphinais, G.William; Means, Grady; Price, Colin (New York : John Wiley, 2000)
Business
Keywords: CEO; Business leadership; Innovation; E-business; Knowledge management